I guess I'll get the papers and go home the life of Doc Cheatham - Cheatham, Doc 1905-1997 (Cassell, 1996)
In the Big Band era, Cheatham played with McKinney's Cotton Pickers and Teddy Wilson's Orchestra as well as Calloway, and gives a fascinating insider's view of the life of a black jazz musician in the swing era. Later, Cheatham worked in Latin American bands before revitalizing his jazz career in the 1960s to become a much-in-demand soloist, famous for his work with Benny Goodman and Lionel Hampton, as well as with his own Quartet, resident for many years at New York's Sweet Basil